Efforts to increase literacy at the parangtambung lorong library in Makassar, Indonesia - Irwan, Andi Muhammad; Sapriyadi, Sapriyadi; R, Paramita (Community Empowerment, 2021)
The society's relatively low reading interest is one of the problems faced by Indonesia. This condition can have an impact on socio-cultural conditions such as the habit of indulging in meaningless conversations. In Makassar City, various efforts have been made by stakeholders to overcome these problems. One of them is by establishing a hallway library in Parangtambung Village. The purpose of this activity is to educate the public about the importance of strengthening literacy through increasing reading interest. The method used was socialization and discussion. The Parangtambung hallway library can be used as a source of information and a source of knowledge which is expected to increase public interest in reading. After discussion, it was found that the cause of the low interest in reading in the community was due to the incompatibility of several types of books with the information needs of the community. Besides, the large potential for community entrepreneurship has encouraged the service team to add to the collection of books on entrepreneurship themes. The service team also provides motivation in fostering an entrepreneurial spirit. In addition, activities were enhanced with materials on business management and development through product innovation and digital-based marketing strategies.